(3Odjd GdebJfjGJ GdChd(B: (3GdeJMa GdESdGej HGdTGQbI(B/ (3YaGa GdeQj , YKeGf ajOGf s ((3OGFQI GdKbGaI h GdEYdGe, McheI GdTGQbI; s, 2003)
First collectibles guide @Sharjah Museum of Islamic Civilization.
Arabic
Keywords: Islamic Civilization; N5198-5299 Visual Arts- Private collections and collectors